The effect of alpha-tocopherol on the oxidative cleavage of beta-carotene - Yeum, K. J.; Ferreira, ALD; Smith, D.; Krinsky, N. I.; Russell, R. M. (Elsevier B.V., 2000)
Two cleavage pathways of beta-carotene have been proposed, one by central cleavage and the other by random (excentric) cleavage. The central cleavage pathway involves the metabolism of beta-carotene at the central double bond (15, 15') to produce retinal by beta-carotene 15, 15'-dioxygenase (E.C.888990988). The random cleavage of beta-carotene produces beta-apo-carotenoids, but the mechanism is not clear. To understand the various mechanisms of beta-carotene cleavage, beta-carotene was incubated with the intestinal postmitochondrial fractions of 10-week-old male rats for 1 h and cleavage products of beta-carotene were analyzed using reverse-phase, high-performance liquid chromatography (HPLC). We also studied the effects of alpha-tocopherol and NAD(+)/NADH on beta-carotene cleavage. In addition to beta-carotene, we used retinal and beta-apo-14'-carotenoic acid as substrates in these incubations. Beta-apo-14'-carotenoic acid is the two-carbon longer homologue of retinoic acid. In the presence of alpha-tocopherol, beta-carotene was converted exclusively to retinal, whereas in the absence of alpha-tocopherol, both retinal and beta-apo-carotenoids were formed. Retinoic acid was produced from both retinal and beta-apo-14'-carotenoic acid incubations only in the presence of NAD(+). Our data suggest that in the presence of an antioxidant such as alpha-tocopherol, beta-carotene is converted exclusively to retinal by central cleavage. In the absence of an antioxidant, beta-carotene is cleaved randomly by enzyme-related radicals to produce beta-apo-carotenoids, and these beta-apo-carotenoids can be oxidized further to retinoic acid via retinal. (C) 2000 Elsevier B.V.
Keywords: central cleavage; random cleavage; oxidation products; retinal; retinoic acid; beta-carotene; beta-apo-carotenoids; beta-carotene 15; 15 '-dioxygenase; free radicals